Differentiating root and rhizome of panax notoginseng based on precursor ion scanning and multi heart‐cutting two‐dimensional liquid chromatography. Issue 2 (29th November 2022) - Yang, Yuangui; Jin, Yan; Zhang, Yanhai; Wang, Zhengtao
Abstract : Owing to increasing demand for Panax notoginseng‐ based medicines and health products, establishing a fast, simple, and reliable assay to analyze the chemical differences between its root and rhizome is important. Although previous studies showed that the chemical and biological differences between the root and rhizome of P. notoginseng seem to be small, efforts should be taken to investigate such differences to ensure the safety and efficacy of the products. This work describes a holistic approach that combines characteristic fingerprinting using ultra‐high performance liquid chromatography‐tandem mass spectrometry parent ion scanning with charged aerosol detection and targeted separation by online heart‐cutting two‐dimensional liquid chromatography, to identify and evaluate characteristic markers allowing differentiation of the root and rhizome. A total of five potential markers chikusetsusaponin L5, ginsenoside Rb2, stipuleanoside R2, malonyl‐ginsenoside Rb1, and malonyl‐ginsenoside Rd, were identified and confirmed by comparing chromatographic retention time, the accurate mass of molecular weight, and the fragments of secondary MS with the available reference materials. The results showed that all five markers were 2.8–7 times higher in content in the rhizome than in the root.